Crystal structure of 4-(4-(1H-imidazol-1-yl)phenyl)-2,6-diphenylpyridine, C26H19N3 - Wu Y.-Z.; Wang C.-X.; Yu W.-T.; Yang J.-X. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C26H19N3, monoclinic, P121/c1 (no. 14), a = 12.885(1) Å, b = 15.007(2) Å, c = 10.863(2) Å, β = 109.460(8)°, V = 1980.4 Å3, Z = 4, Rgt(F) = 0.060, wRref(F2) = 0.184, T = 293 K.